Metabolite Storage in Theobroma cacao L. Seed: Cyto-Histological and Phytochemical Analyses - Cerri, Martina; Reale, Lara; Zadra, Claudia (Frontiers in Plant Science, 2019)
Cocoa (Theobroma cacao L.), an economically important tropical-fruit crop as source of chocolate, has recently gained a considerable attention; its seeds contain a large amount of different bioactive compounds that have attracted interest because may be beneficial to humans by improving cardiovascular health, by cancer chemo-preventive effects and also through neuroprotective activities. The morphological and anatomical characteristics of cocoa seeds are closely related to the aroma and to the nutritional properties. This study aimed to provide more information about the storage of some metabolites in the various components of cocoa seed by microscopical and phytochemical analyses. Polyphenols, sterols, tocopherols and fatty acids were detected in different portions of the seeds (teguments, cotyledons, embryo axis and pulp). Quali and quantitative differences were observed and a characteristic polyphenol pattern was detected in the different portions of the seed; cytological analysis demonstrated the presence of these compounds in big vacuolated polyphenolic cells. Among the analyzed fatty acids, the stearic and oleic acids were the most abundant in all the seed components (teguments, cotyledons and embryo axis). Fatty acids, either free or as part of complex lipids, are important constituent of membranes or other cellular structures but also represent one of the storage substances of cocoa seed probably localized in lipid globules, which in our observations occupied almost the entire volume of small isodiametric cells of cotyledon mesophyll. In the cocoa seeds we observed also a different distribution of sterols: -sitosterol and 5-avenasterol were the most abundant, above all in the embryo axis; stigmasterol and campesterol were less present in embryo axis and more abundant in teguments; campestanol level was again higher in teguments but lower in cotyledons. The specific localization of different kind of sterols was probably related to a peculiar function. Our experiments demonstrated that all seed components contribute to the metabolites storage, but with interesting differences in the localization and amount of each metabolite.